2021
DOI: 10.3389/fimmu.2021.759323
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Serum Metabolome and Gut Microbiome to Evaluate the Benefits of Lauric Acid on Lipopolysaccharide- Challenged Broilers

Abstract: Lauric acid (LA) is a crucial medium-chain fatty acid (MCFA) that has many beneficial effects on humans and animals. This study aimed to investigate the effects of LA on the intestinal barrier, immune functions, serum metabolism, and gut microbiota of broilers under lipopolysaccharide (LPS) challenge. A total of 384 one-day-old broilers were randomly divided into four groups, and fed with a basal diet, or a basal diet supplemented with 75 mg/kg antibiotic (ANT), or a basal diet supplemented with 1000 mg/kg LA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 70 publications
3
22
0
Order By: Relevance
“…In this study, we demonstrated that LP postbiotics, particularly the metabolites, exhibited a stronger capacity in alleviating Salmonella -induced injuries, as evidenced by the significant inhibition of weight loss, suppression of ST translocation, and alleviation of tissue injuries and neurological dysfunctions. Consistently with our findings, it was reported that Lactobacillus -derived postbiotics showed immunomodulatory and protective capacity against Salmonella infection in mice ( 30 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, we demonstrated that LP postbiotics, particularly the metabolites, exhibited a stronger capacity in alleviating Salmonella -induced injuries, as evidenced by the significant inhibition of weight loss, suppression of ST translocation, and alleviation of tissue injuries and neurological dysfunctions. Consistently with our findings, it was reported that Lactobacillus -derived postbiotics showed immunomodulatory and protective capacity against Salmonella infection in mice ( 30 ).…”
Section: Discussionsupporting
confidence: 93%
“…The concentration of SCFAs (acetatic acid, propionic acid, butyric acid, isobutyric acid, valeratic acid, and isovaleric acid) was detected using the headspace sampler gas chromatography based on our previous study ( 30 ). Briefly, 0.3-g cecal contents from each sample were diluted with 1.2 ml sterile water and centrifuged at 12,000 g for 10 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…However, decreased Olsenella in MMT group was positively correlated with MDA, MPO, NO, DAO, and D-LA, and negatively correlated with IgG, IgA, IgM, T-SOD, T-AOC, and CAT. Consistently, it was reported that Bacteroides could significantly reduce the fasting hyperglycemia and high plasma concentrations of proinflammatory cytokines in mice [ 60 ], and exhibited a marked anti-inflammatory activity against E.coli -induced IL-8 release, and showing that an increased abundance of Bacteroides might suppress inflammatory responses [ 61 , 62 ]. Furthermore, the antioxidant and immune functions were positively correlated with the pyruvate metabolism, ribosome, glycolysis/gluconeogenesis, and pyrimidine metabolism of microbial communities, but negatively with metabolic pathways, microbial metabolism, and carbon metabolism of microbial communities.…”
Section: Discussionmentioning
confidence: 59%
“…Barnesiella has an immunomodulatory effect, which can prevent the colonization of drug-resistant pathogens in the intestine [ 30 ]. The increase of Barnesiella abundance is beneficial to improving the resistance of broilers to lipopolysaccharide challenge, alleviating inflammatory response [ 31 ]. Inflammation is an important factor inducing and aggravating hepatic steatosis in chicken [ 32 ].…”
Section: Discussionmentioning
confidence: 99%